Localized tetanus treated with kampo medicines. Issue 2 (25th March 2018) - Nakae, Hajime; Satoh, Kasumi; Okuyama, Manabu; Furuya, Tomoki
ABSTRACT: Case: A 73‐year‐old woman with a history of generalized tetanus and hypertension developed localized tetanus. Daisaikoto (DST) was used to control spasming of cervical muscles given the symptom of tenderness observed on both sides of her abdomen, kyokyo‐kuman. All symptoms except for cheek discomfort were improved. On day 7, shakuyakukanzoto (SKT) was given to control the residual symptoms. Outcome: Residual symptoms improved after treatment with DST and SKT. Conclusion: DST can be used for the management of muscle spasms in localized tetanus, based on the oriental medical syndromes.